Endoscopic Management of Maxillary Antral Diseases - Biswas, Supran; Khan, Md Mozibul Hoque; U, Kyaw Khin; Pramanik, Kamol Krishna; Datta, Pranay Kumar (Journal of Chittagong Medical College Teachers’ Association, 2017)
Background : To see effectiveness of Endoscopies sinus surgery and it’s complication for the management of maxillary antral diseases. Materials and methods : A cross sectional observational study conducted from August’2014 to February’2016 in Otolaryngology Department, Chittagong Medical College Hospital, Chittagong. Results : The age of majority of the patients range from 21-30 years. Male and female patients were equal in number (M.F=1.1). The presenting symptoms of the patients were nasal obstruction, nasal discharge, headache, post nasal space drip, smell disturbance, recurrent sore throat and epistaxis. Major indications were chronic maxillary sinusitis 14 (46.67%), antrochoanal polyp 9(30%). Minor complication occurred in 9(30%) cases which included synechiae 3(10%) epistaxis 3(10%) and periorbital echymosis 3 (10%). Conclusion : No serious complications like CSF leak, retro orbital hemorrhage, blindness were noted. JCMCTA 2017 ; 28 (1) : 27 - 31